Green practices for sustainability of quick service chain restaurants business: an empirical investigation. (2018) - Nigam, Ashutosh; Kumari, Sima
Indian quick service chain restaurants are becoming an important segment of food services market and have seen exponential growth in India. To survive and sustain in longer term, organised quick service chain restaurants have to develop policy and processes towards green practices and are able to make significant contribution towards community development. The present study focuses on employees' behaviour towards green practices in quick service chain restaurants with broadly three prospective namely, environmental, social and economic. Adoption of green practices will enable the QSR to sustain the business persistently and able to grow their businesses through community development.